PENERAPAN ALGORITMA C4.5 UNTUK MEMPREDIKSI PENCAPAIAN PROFIT PADA PT INDOLAND BATAM - juppren, juppren; Arnomo, Sasa Ani (LPPM Universitas Putera Batam, 2021)
The development of technology and information has changed all fields, including the development of the business world. It is hard to deny that the rapidly developing technology is currently attracting the attention of many people, including online shop business people. An online store business must calculate important information to run the business plan it manages every year. PT Indoland Batam is a company engaged in online sales or online stores that offer products such as men's and women's clothing, men's and women's wallets, men's and women's bags, men's and women's shoes, and household goods. The company started operations in 2017 and is located at Citra Buana Industrial Park 1, Blok H No 1-2, Jalan Yos Sudarso, Kampung Seraya Batam. In 1 month PT Indoland Batam can sell around 15,000 packages up to 20,000 packages but due to changes in customs regulations that affect shipping or expeditions where every package delivery from Batam is subject to a large tax, it causes a very drastic decline in package sales.